Analisis Pengaruh Faktor-Faktor Fundamental Terhadap Harga Saham (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2012 – 2015) - x, Ivan (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
In efficient market theory it is mentioned that a price change of a stock's securities in the past can not be used to estimate price changes and the theory of signals is also mentioned that investors see signs made by managers of firms to predict future outlook. Therefore, the research was made to obtain empirical evidence by analyzing whether the fundamental factor has significant effect on stock price in manufacturing companies either partially or simultaneously on manufacturing companies listed on BEI in 2012-2015. The fundamental factors here are divided into profitability, solvency and liquidity are represented by ROA, ROE, NPM, DER, CashTA, TATO, and EPS ratios. Research using Data Panel Regression assisted with Eviews program. The results of research partially only NPM, CashTA and EPS variables that have a significant effect while for the variable ROA, ROE, DER and TATO no significant effect. Simultaneously all the variables together have a significant influence on stock prices.